Research progress in Pusher Syndrome after stroke - Wu, Huayong; Duan, Haoyang (Frontiers in Neurology, 2025)
Post-stroke Pusher Syndrome is a postural control disorder. It is characterized by active tilting toward the hemiplegic side and resistance to correction. This significantly impacts patients’ motor function and quality of life. Its incidence varies greatly due to different research designs and assessment criteria. Literature reports an incidence ranging from 5% to 63%, and the incidence in patients with right brain damage (17.4%) is much higher than that in patients with left brain damage (9.5%). Etiological studies indicate that damage to the parietal lobe, thalamus, insula, and postcentral gyrus is the main pathological basis. The key mechanism is the interruption of thalamocortical connections. Typical clinical manifestations include trunk tilting in supine position, asymmetric weight-bearing in sitting, weight shift in standing, and impaired weight transfer during gait. Patients often have unilateral spatial neglect, which exacerbates balance disorders. Prognosis shows about 90% of patients recover within 6 months, but 10% to 15% may have long-term symptoms. Early rehabilitation intervention can significantly improve functional outcomes. This article comprehensively reviews the nomenclature, incidence, etiology, lesion sites, clinical manifestations, and prognosis of Pusher Syndrome, providing a research foundation for future studies on post-stroke Pusher Syndrome.